Interaction of the adenovirus L1 52/55-kilodalton protein with the IVa2 gene product during infection - Gustin, K E; Lutz, P; Imperiale, M J (Journal of virology, 1996)
The adenovirus L1 52/55-kDa protein is expressed both in the early and late stages of infection, raising the possibility that it has multiple roles in the viral life cycle. To obtain possible insights into these roles, the yeast two-hybrid system was used to examine the interactions of the 52/55-kDa protein with viral and cellular factors. cDNA expression libraries from human 293 cells at both early and late stages of adenovirus type 5 infection were constructed and screened, with the 52/55-kDa protein being used as bait. Characterization of positive clones revealed that the adenovirus IVa2 gene product interacted specifically with the 52/55-kDa protein. In addition, the IVa2 protein was shown to interact with a bacterial glutathione S-transferase-52/55-kDa fusion protein in vitro, further supporting the finding with the yeast two-hybrid system. Finally, coimmunoprecipitation studies confirmed that the 52/55-kDa protein and IVa2 polypeptide interact specifically during the course of adenovirus infection. A potential role for the IVa2-52/55-kDa protein interaction in the regulation of transcription from the major late promoter and in viral assembly is discussed.